Effect of Polymer Film Coating with Pesticides and Storage Containers on Longevity of Wheat Seeds - AVINASH KARJULE; KALYAN RAO; DA PATEL; VB DARJI (Seed Research, 2026)
A two years storage study was conducted for evaluation of polymer film coating along with insecticide, fungicide, storage containers and storage duration effect on storability of wheat seed. Seed treated with combination of Deltamethrin 2.8 EC @ 0.5 ml/kg seed + Vitavax power @ 2.5 g/kg seed + Polymer seed coating @ 5 ml/kg seed stored in HDPE bag for three months recorded significantly higher pooled average field emergence (90.61%), germination (92.64%), seedling vigour index I (1319) and seedling vigour index II (13.17). The seeds without any treatment stored in cloth bag for nine months recorded significantly lower seed quality parameters. Higher seed quality was maintained in HDPE bag mainly due to controlled moisture inside the bag. Seed deterioration rate was faster in the seeds stored in cloth bag. All the seed quality attributes declined gradually with the advancement of the storage period during both the years. The seed germination (87.70%) was maintained above Indian Minimum Seed Certification Standards up to 6 months of storage.